Applications of quantum and classical connections in modeling atomic, molecular and electrodynamic systems - Popa, Alexandru (Alexandru Mircea) (Academic Press, 2014)
This book connects the properties of quantum equations to corresponding classical equations used to calculate the energetic values and the symmetry properties of atomic, molecular and electrodynamical systems.